Hepatitis C Virus Infection in Pregnant Women - Current Treatment Practices - Zapalska, Magdalena; Krupska , Barbara Izabela; Malec , Julia Anna; Kulig, Lidia; Włodarczyk, Franciszek; Woźniak, Weronika Maria; Wieleba, Marcin; Winiarska, Zuzanna; Witczak, Katarzyna Wiktoria; Wiercioch, Eliza (Quality in Sport, 2026)
Hepatitis C Virus (HCV) is a single-stranded RNA virus with hepatotropic potential classified within the Flaviviridae family. HCV infection still remains a global problem. According to the World Health Organisation (WHO), about 50 million people were chronically infected in 2025. Available data suggest that the number of seropositive births fluctuates between 2,2 to 5,5 million worldwide. The therapy of hepatitis C during pregnancy continues to be a challenge, in light of the risk of theratogenic effects that may carry. Matherials and methods. The literature review was conducted using databases: Scopus and Pubmed. The review included the recent years publications and analysis of six different clinical trials focused on the safety and efficacy of the HCV infection treatment during pregnancy with Direct-Active Antivirals (DAAs). Results. According to the results of analyzed in this review clinical trials it can be concluded that DAAs therapy is effevctive. Various combinations of DAAs, including Sofosbuvir/Velpatasvir and Sofosbuvir/Ledipasvir showed similar therapeutic potential and safety for women and their newborns. Conclusions. More clinical trials in larger groups of pregnant patients should be performed to understand the effectivenes and safety of the DAAs therapy among women in pregnancy. Available results of conducted research show that Direct-Active Antivirals are well-tolerated and they reduce the risk of mother-to-child-transmission of the HCV.